The third language imitation of Spanish rhotic-lateral contrast by Akan-English bilingual children and adults: the effect of first language transfer, orthography, and age of acquisition - Ahima, Linda; Loyola, Gabriela Martinez; Spinu, Laura; Rafat, Yasaman (Journal of Speech Sciences, 2023)
This study explores the third language imitation of the Spanish rhotic-lateral contrast by Akan-English bilingual children and adults. Specifically, it examines this phenomenon, with respect to (i) first language transfer in the imitation of the Spanish rhotic-lateral contrast, (ii) the effect of orthographic input on the imitation of the rhotic-lateral contrast in Spanish as a third language, and (iii) the effect of age of acquisition with the inclusion of a comparison between children and adults. Whereas rhotics and laterals are contrastive in most varieties of Spanish and English, they are in free variation in Akan (Guerini, 2018). The participants in this study consisted of 20 Akan-English bilinguals between the ages of 8-10yrs and 18-55. The conditions included an imitation task with auditory input only and another with orthographic input. The results showed evidence of L1 transfer, a positive effect of orthography, and a better performance of children. This study has important implications as it provides data from an understudied population in the field of L2/L3 speech learning.